The impact of silica encapsulated cobalt zinc ferrite nanoparticles on DNA, lipids and proteins of rat bone marrow mesenchymal stem cells - Novotna, Bozena; Turnovcova, Karolina; Veverka, Pavel; Rössner, Pavel; Bagryantseva, Yana; Herynek, Vit; Zvatora, Pavel; Vosmanska, Magda; Klementova, Mariana; Sykova, Eva; Jendelova, Pavla (Nanotoxicology, 2016)
Nanomaterials are currently the subject of intense research due to their wide variety of potential applications in the biomedical, optical and electronic fields. We prepared and tested cobalt zinc ferrite nanoparticles (Co0.5Zn0.5Fe2O4+γ [CZF-NPs]) encapsulated by amorphous silica in order to find a safe contrast agent and magnetic label for tracking transplanted cells within an organism using magnetic resonance imaging (MRI). Rat mesenchymal stem cells (rMSCs) were labeled for 48 h with a low, medium or high dose of CZF-NPs (0.05; 0.11 or 0.55 mM); silica NPs (Si-NPs; 0.11 mM) served as a positive control. The internalization of NPs into cells was verified by transmission electron microscopy. Biological effects were analyzed at the end of exposure and after an additional 72 h of cell growth without NPs. Compared to untreated cells, Annexin V/Propidium Iodide labeling revealed no significant cytotoxicity for any group of treated cells and only a high dose of CZF-NPs slowed down cell proliferation and induced DNA damage, manifested as a significant increase of DNA-strand breaks and oxidized DNA bases. This was accompanied by high concentrations of 15-F2t-isoprostane and carbonyl groups, demonstrating oxidative injury to lipids and proteins, respectively. No harmful effects were detected in cells exposed to the low dose of CZF-NPs. Nevertheless, the labeled cells still exhibited an adequate relaxation rate for MRI in repeated experiments and ICP-MS confirmed sufficient magnetic label concentrations inside the cells. The results suggest that the silica-coated CZF-NPs, when applied at a non-toxic dose, represent a promising contrast agent for cell labeling.
Keywords: Animals; Microscopy, Electron, Transmission; Magnetic Resonance Imaging; proliferace buněk; DNA Damage; vztah mezi dávkou a účinkem léčiva; Silicon Dioxide; mezenchymální kmenové buňky; cytotoxicity; kobalt; Protein Carbonylation; Nanoparticles; povrchové vlastnosti; Staining and Labeling; genotoxicity; železité sloučeniny; Lipid Metabolism; magnetická rezonanční tomografie; dinoprost; barvení a značení; sloučeniny zinku; nanočástice; kultivované buňky; Contrast Media; metabolismus lipidů; Mesenchymal Stem Cells; Cells, Cultured; Dose-Response Relationship, Drug; poškození DNA; Isoprostanes; kontrastní látky; karbonylace proteinů; protein oxidative damage; Cell Proliferation; oxid křemičitý; krysa rodu Rattus; Dinoprost; buněčné kultury; Cell Survival; transmisní elektronová mikroskopie; zvířata; Cell Culture Techniques; viabilita buněk; Zinc Compounds; Cobalt; Surface Properties; isoprostany; Rats; Ferric Compounds; Comet assay; lipid peroxidation